Adaptive management of natural resources: theory, concepts, and management institutions. - Stankey, George H.; Clark, Roger N.; Bormann, Bernard T. (U.S. Department of Agriculture, Forest Service, Pacific Northwest Research Station, 2005)
This report reviews the extensive and growing literature on the concept and application of adaptive management. Adaptive management is a central element of the Northwest Forest Plan and there is a need for an informed understanding of the key theories, concepts, and frameworks upon which it is founded. Literature from a diverse range of ﬁelds including social learning, risk and uncertainty, and institutional analysis was reviewed, particularly as it related to application in an adaptive management context. The review identiﬁes opportunities as well as barriers that adaptive management faces. It concludes by describing steps that must be taken to implement adaptive management.

Donors' Learning Difficulties: Results, Relationships and Responsibilities - Eyben, Rosalind (IDS Bulletin, 2005)